Gastrointestinal stromal tumors of the stomach in a 10-year-old child - Saeed Nasher; Fayed Al-Yousofy; Faisal Ahmed (Elsevier, 2021)
Gastrointestinal stromal tumor (GIST) appears to occur extremely rare in children and adolescents with unpredictable behavior. It accounts for about 0.2% of all gastrointestinal (GI) tumors. Herein, we reported a 10-year-old male child with epigastric pain and tiredness from the year before. The patient had a history of repeated blood transfusion in the previous year and had been diagnosed with idiopathic chronic anemia. Computed tomography (CT) of the chest and abdomen showed well-defined sub-epithelial hypodense soft tissue masses measuring 62 × 31 mm located in distal part of the stomach without metastases. The upper GI endoscopy relived two polypoid submucosal smooth masses located at the distal part of stomach, which were associated with ulceration and bleeding. The biopsy was carried out, but was inconclusive. Immunohistochemistry (IHC) study showed GIST with intermediate risk. Partial gastrectomy and tumor resection was performed followed by adjuvant imatinib mesylate chemotherapy. The present report mainly aimed to draw attention of physicians to consider the GIST tumor diagnosis when facing an unusual manifestation of chronic anemia not responding to treatments, specifically in children among whom the prevalence of this disease is rare.